Study the Situation of Social Security in the Side Walk Construction in Ardebil City - Mohamadhasan Yazdani; Anahita Sedehg; Asghar Pashazadeh (جغرافیا و توسعه, 2016)
One of the most important urban spaces that citizens, in addition to leisure time will use for supplying the life requirements, social interaction and so on are the urban sidewalks. Choosing the side walk routes need to indices that in addition to increasing access and safety for citizens could also provide them social security. In this regard, the present study has evaluated the mausoleum of Sheikh Safi up to Ardabil Jomeeh mosque in order to achieve the sidewalk area. The main aim of this study is to recognize the effective indices on the side walks from the view of citizens in order to study the relevance of the under study area for creating the side walk axis. The present study is of descriptive-analytical one and from the objective point of view has functional aspect. Ardebil citizens form the study population of the research and by Cocran Formula, 383 people chosen as sample and questionnaire randomly distributed between them. For analysis, single-sample t-test (Klvmvgrvf- Smirnov test to check for normal distribution), t-test independent, one way variance and multivariate regression were used. The findings suggest that, if side walk is constructed in this area, this side walk will be in an inappropriate conditions in terms of social security. Also the age and education level of those questioned was effective in their perception about quality of sidewalk. And regarding the effective criteria on the quality of sidewalk, the multiple regressions showed that about 85.1 percent of the side walks' quality variance define the ninth criteria of the  research. So that urban services with 68.8 percent was placed at the first rank and the economic impact by 0.032 percent placed at the last rank of the ninth criteria of the research.